Mental Health in Altruism Scenarios: Coping Strategies in Volunteers of The Civil Defense of The Mojana Sucreña Area – Colombia (2024)
Introduction: Coping strategies are of vital importance for Civil Defense volunteers because they can cope with the stress and emotional demands associated with their work, ensuring their well-being and their ability to provide quality assistance to affected communities. Objective: To describe the coping strategies used by the volunteers of the Colombian Civil Defense - Mojana Sucreña area during natural disasters. Method: Research framed under a positivist paradigm, quantitative descriptive type, the population chosen were 148 volunteer leaders of the Civil Defense to whom the modified Coping Strategies Scale (EEC-M) was applied to identify the strategies most used by these leaders when facing a calamity where their urgent intervention is required. Results: The strategies most used by the volunteers by factors were: religion (79.7%) and seeking professional support (79.1%), which indicates that the volunteers cling to God and seek the opinion of a professional to resolve any conflict that may arise. Now, the most limited strategy by the volunteers is the expression of the difficulty of Coping (70.3%) and Denial (64.2%) which means that it is difficult for them to express their difficulties. Conclusion: Keep in mind that each person has different ways of coping with stress and adverse situations. Some strategies may be more effective than others, and it is essential to provide Civil Defense volunteers with the necessary tools and support to develop adaptive coping strategies